Age-related effects on dynamic postural stability and prefrontal cortex activation during precision fitting tasks - Jiahao Pan; Hui Tang (PeerJ)
Background Dynamic postural control is impaired in older adults, as evidenced from worse dynamic postural stability compared to young adults during upright stance while concurrent goal-directed tasks. Prefrontal cortex (PFC) is considered to play an important role in goal-directed tasks. This study aimed to investigate the age effects on dynamic postural stability and PFC activation during precision fitting tasks. Methods Participant performed precision fitting tasks under four different conditions: large opening size with their arm’s length (close-large), small opening size with their arm’s length (close-small), large opening size with 1.3 times arm’s length (far-large), and small opening size with 1.3 times arm’s length (far-small). We analyzed the center of pressure-related outcomes representing dynamic postural stability and PFC activation at the six different subregions from healthy older adults (n = 15, 68.0 ± 3.5 years), and gender-matched middle-aged (n = 15, 48.73 ± 3.06 years) and young (n = 15, 19.47 ± 0.64 years) adults. Results The dynamic postural stability presented the young > middle-aged > older groups across the conditions. Specifically, the young group presented better dynamic postural stability than the older group in the close-large, far-large, and far-small conditions (p < .05), while showed better dynamic postural stability than the middle-aged group in the close-large condition (p < .05). Additionally, the older group had greater PFC activation at all PFC subregions than the young group (p < .05), while had greater activation at left dorsolateral and ventrolateral PFC than the middle-aged group (p < .05). The middle-aged group presented greater activation at left dorsomedial PFC than the young group (p < .05). Conclusion Heightened dorsomedial PFC activation in middle-aged adults compared to young adults may reflect a deficit in processing the visuomotor information during the precision fitting tasks. Degeneration of the ability in automatic coordination of dynamic postural control may begin to occur at midlife.